THE FORMATION CONCEPTUAL BASIS OF ACCOUNTING POLICY FOR DEFERRED REVENUE IN ACCORDANCE TO IFRS 15 «REVENUE FROM CONTRACTS WHITH CUSTOMERS» (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Abstract. The article provides a scientific justification of the methodological basis of accounting policies for deferred income and the features of their recognition over time, taking into account the requirements of IFRS 15 «Revenue from contracts whith customers». A method of recognizing revenue from contracts with customers over time is assessed, assessing progress towards full compliance with the obligation to perform. Approaches to the reflection of modifications of the contract and a significant component of financing are formalized.A conceptual accounting model is proposed to disclose information in the financial statements about contractual assets and liabilities. Prerequisites for harmonization of financial statements with the requirements of international standards have been formed.
Keywords: deferred revenue, contractual assets, contractual liabilities, contract modification, significant financing component